REPRICING AS STRATEGIES TO SURVIVE IN THE HOSPITALITY BUSINESS DURING THE PANDEMIC OF COVID-19 (Case Study at Wyndham Garden Kuta Bali) - Bangun Mulia, Victor (Brilliant International Journal Of Management And Tourism, 2022)
This study aimed at analysing the pricing strategy done by Wyndham Garden Kuta Bali as one of the strategies to survive during the pandemic. This was a qualitative research using interview and literature study to collect the data. The interview was done with the general manager of Wyndham Garden Kuta Bali, while literature study was done by analyzing several relevant literatures. Data gained from the interview and literature study were analyze qualitatively by doing data sorting and organizing. Based on the results of analysis, it was found out that pricing was done by the executive committee and owner. The re-pricing done by Wyndham Garden Kuta Bali affected the occupancy in which there was an increase in term of occupancy in 2022. Even though the increase was not that significant, it might be good indicator for the improvement of tourism and hospitality industry in Bali.